2012
DOI: 10.1007/s00414-012-0701-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of Gustafson’s criteria for the purpose of forensic age diagnostics

Abstract: The main criteria used in dental age estimation in living young individuals are mineralisation and eruption of the third molars. In order to further diversify the spectrum of characteristics after completion of third molar development, tests were undertaken to determine whether the characteristics studied by Gustafson can be ascertained with the required forensic certainty with the aid of the orthopantomogram and whether the evaluation of these could render forensic odontological age diagnoses possible beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 26 publications
1
22
0
12
Order By: Relevance
“…However, after the permanent dentition is established, typically at around 14 years of age, age estimation becomes increasingly difficult, and assessment of the mineralization of the third molars is the method of choice [26]. A study using this method on German individuals aged 15–40 years reported a standard error in age estimation of 5.3–5.7 years [27]. However, the use of this method in adults, particularly after middle age, is still controversial [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, after the permanent dentition is established, typically at around 14 years of age, age estimation becomes increasingly difficult, and assessment of the mineralization of the third molars is the method of choice [26]. A study using this method on German individuals aged 15–40 years reported a standard error in age estimation of 5.3–5.7 years [27]. However, the use of this method in adults, particularly after middle age, is still controversial [28].…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which decedents and injured migrants coexisted, additional information about the victims was derived from the inpatients of the same border crossing group. The estimation of age in cadavers was performed by using the Gustafson dental method of aging , while through utilizing human skeletal remains, the aging of the victims was performed with reference to the existence and the extent of synostosis of the cranial sutures and epiphyses (cranial suture closure and epiphyseal closure method) . Βiological material was obtained from all unidentified cadavers for their possible subsequent identification through DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past 20 years, scientific insights gained in the field of age diagnosis in living persons have been mainly inspired in an almost unprecedented manner by the specific requirements of practical forensic work [1][2][3][4][5][6]. However, application of the results of this development is not restricted to conventional medical and legal contexts.…”
Section: Introductionmentioning
confidence: 98%